2018
DOI: 10.1177/1538574418772459
|View full text |Cite
|
Sign up to set email alerts
|

High Reintervention and Amputation Rates After Outpatient Atherectomy for Claudication

Abstract: Outpatient use of atherectomy for peripheral arterial disease has grown rapidly and outcomes are poorly understood. We analyzed outcomes of atherectomy done for claudication, comparing office and hospital outpatient settings. Analysis of Medicare Part B claims data was performed for incident femoral-popliteal or tibial-peroneal atherectomy from 2012 to 2014. Longitudinal analysis assessed services 18 months before, during, and up to 18 months after the incident peripheral vascular intervention (PVI). Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The more conservative practice patterns we found in our study also likely reflect a number of other factors, including increasing knowledge of the outcomes of medical management and walking programs 8,9 ; Medicare reimbursement of supervised walking programs, which was newly established beginning in 2018 21 ; and awareness of the complications associated with PVI in patients with an otherwise low risk for limb loss, including need for reintervention or major amputation. 11,22 Importantly, patients do not accept the risks associated with interventions for claudication; in a survey of 50 patients with claudication, the median risk acceptance for major amputation and death as a complication was 0%. 23 Furthermore, there was no association between shorter walking distance and greater acceptance of amputation risk with treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more conservative practice patterns we found in our study also likely reflect a number of other factors, including increasing knowledge of the outcomes of medical management and walking programs 8,9 ; Medicare reimbursement of supervised walking programs, which was newly established beginning in 2018 21 ; and awareness of the complications associated with PVI in patients with an otherwise low risk for limb loss, including need for reintervention or major amputation. 11,22 Importantly, patients do not accept the risks associated with interventions for claudication; in a survey of 50 patients with claudication, the median risk acceptance for major amputation and death as a complication was 0%. 23 Furthermore, there was no association between shorter walking distance and greater acceptance of amputation risk with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Notably, both sets of guidelines cited the very low risk of progression of claudication to chronic limb-threatening ischemia, 8,9 with major amputation occurring in <5% of affected patients after 10 years of follow-up. 10 In contrast, a recent study of Medicare beneficiaries found that 4.1% of patients undergoing outpatient atherectomy for claudication required subsequent major amputation within just 1.5 years, 11 suggesting that PVI carries a risk for limb loss that may be worse than the natural history of medically managed claudication.…”
mentioning
confidence: 97%
“…One new solution is atherectomy, where the plaque is removed using endovascular techniques. However, one study showed high rates of amputation after one year 63 and another study showed a high rate of long-term adverse events with atherectomy compared to stent . One of the most prominent new solutions during the past decade have been the use of drug-coated stents and balloons that were developed to mitigate restenosis after endovascular treatment.…”
Section: 2c Invasive Treatment: Evidencementioning
confidence: 99%
“…A second study by Mukherjee et al 7 identified higher than expected amputation rates compared to the natural history of the disease irrespective of the site of service when claudicants were treated with atherectomy. There was also a high rate of reintervention.…”
mentioning
confidence: 97%
“…The data mined from Medicare is not granular enough to identify the device used, define the indication of the procedure, the side of the procedure, or the medical management carried out prior to the procedure. All the aforementioned articles 510 that mined data from Medicare could not differentiate between various devices, so accurate conclusions could not be drawn.…”
mentioning
confidence: 99%